Microwave and Blanching Pretreatments for Hot Air Drying of Orange-Fleshed Sweet Potato Slices (Ipomoea batatas) - Ernest Abano (International Journal of Food Science)
Microwave and steam blanching as pretreatments to hot air drying of orange-fleshed sweet potato (OFSP) were studied. The air-drying experiment was performed at constant temperature of 70°C and airflow of 1.0 m/s. The effective moisture diffusivity varied from 1.5×10−9 to 4.4×10−9 m2/s, and 1.1×10−10 to 7.9×10−10 m2/s, for the microwave and blanched assisted hot air drying, respectively. The activation energy obtained for the various microwave-assisted hot air drying was 29.1 W/mm for 4 min, 68.1 W/mm for 3 min, and 79.7 W/mm for 2 min. Ascorbic acid degradation and formation of brown pigments in the OFSP slices were lower in microwave than in steam blanch-assisted drying. Microwave-assisted drying of OFSP is best governed by Page model, MR=exp−ktn, while the blanch-assisted followed the logarithmic model, MR=a exp−kt+c. To produce better quality OFSP flour, it is recommended to cut the tubers into 3 mm slices, microwave at a power of 630 W for 2 min or blanch for 1 min, 43 seconds prior to hot air drying.